2008
DOI: 10.1007/s00774-007-0840-2
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and clinical aspects associated with bone mineral density in Argentine postmenopausal women

Abstract: The aim of this study was to determine genotypes and clinical aspects associated with bone mineral density (BMD) in postmenopausal women from Córdoba, Argentina. Polymorphisms were assessed by RFLP-PCR technique using BsmI and FokI for vitamin D receptor gene (VDR) and XbaI and PvuII for estrogen receptor-alpha gene (ERalpha) as restrictases. Sixty-eight healthy, 54 osteopenic, and 64 osteoporotic postmenopausal women were recruited. Femoral neck and lumbar spine BMD were inversely correlated with age in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 40 publications
4
35
0
Order By: Relevance
“…On the other hand, although several studies in the past have suggested that multiple VDR polymorphisms (including BsmI ) influence the regulation of BMD [12,13,14,15], a more recent multicenter prospective trial [17] involving around 26,000 participants, as well as other studies [18,19], have not confirmed such an association. Two additional studies reported an association between bb genotype with low rather than higher BMD [20,62]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although several studies in the past have suggested that multiple VDR polymorphisms (including BsmI ) influence the regulation of BMD [12,13,14,15], a more recent multicenter prospective trial [17] involving around 26,000 participants, as well as other studies [18,19], have not confirmed such an association. Two additional studies reported an association between bb genotype with low rather than higher BMD [20,62]. …”
Section: Discussionmentioning
confidence: 99%
“…Although this initial finding has been partially withdrawn, in the following years, a large number of studies investigated the potential associations of VDR polymorphisms with BMD in different ethnic populations [4][5][6][7][8][9][10], as well as with other parameters such as bone loss [11,12], fractures [11,13,14] and bone turnover [14][15][16]. However, these studies have provided controversial and inconclusive results due to differences in sample size, ethnic background and age group [17,18].…”
Section: Introductionmentioning
confidence: 94%
“…21 reabsorption (14) . This is an adaptation process performed as a compensation mechanism in order to cover the cation needs of the organism (15) . Serum Ca 2þ levels may be normal or low, according to the extent and degree of Ca 2þ deficiency.…”
Section: Introductionmentioning
confidence: 99%